Influence of the Sodium Salt of 3α,7α-Dihydroxy-12-Oxo-5β-Cholanate on Antimicrobial Activity of Ampicillin In Vitro - Suvajdžić, Ljiljana; Gigov, Slobodan; Rašković, Aleksandar; Stojanović, Srđan; Bekut, Maja; Milanov, Dubravka; Čanak, Ivana; Goločorbin-Kon, Svetlana; Mikov, Momir (Acta Scientiae Veterinariae, 2016)
Background: Multiple resistances to antibiotics are an emergent problem worldwide. Scientists intensively search for new substances with the antimicrobial potential or the mode to restore the activity of old-generation antibiotics. Ampicillin is the antibiotic with the expanded range of antimicrobial activity, but its use has decreased due to the poor absorption and highly developed resistance. In vivo studies showed that ampicillin has better absorption and bioavailability if combined with bile acid salts. The aim of this study was to examine antimicrobial effects of ampicillin alone and its combination with semisynthetic monoketocholic acid salt (MKH) in vitro. Materials, Methods & Results: In this study, commercial preparation of ampicillin and sodium salt of 3α,7α-dihydroxy-12oxo-5β-cholanate were used. Their effects were evaluated on Escherichia coli (E. coli), Enterococcus faecalis (E. faecalis) and Enterococcus faecium (E. faecium), obtained from urine specimens of dogs with clinically manifested cystitis. The first two investigated strains were ampicillin-sensitive, while E. faecium was resistant to ampicillin. Modified macrodilution method according to Clinical and Laboratory Standards Institute Guidelines (M7-A8) was performed. Bacterial suspension equivalent to 0.5 McFarland was prepared in saline, compared to the standard (Biomerieux) ad oculi. The density was checked spectrophotometrically at a wavelength of 625 nm and adjusted if necessary to the desired absorbance from 0.08 to 0.1. The resultant suspension was diluted 1:100 and inoculated in test tubes. Number of bacteria was counted on Petri plates using dilutions from 10-3 to 10-7 in order to obtain valid and countable plates. One hundred microliters of appropriate dilutions were aseptically plated in triplicate onto nutrient agar. Plates were incubated on 37°C for 72 h, under aerobic conditions. The number of colony forming units (CFU) was determined by direct counting. As a valid for enumeration, we took plates with 30 to 300 CFU. Percentage of killed bacteria for ampicillin was from 69.33-95.19% for E. coli, 87.1296.92% for E. faecalis and 7.20-33.30% for E. faecium. Ampicillin applied in the combination with MKH killed 99.99% to 100% of E. coli, 94.59% to 99.91% of E. faecalis and 31.73% to 64.76% of E. faecium. Mean percentage of killed bacteria for ampicillin was 81.93% for E. coli, 91.64% for E. faecalis, and 18.13% for E. faecium, while in combination with MKH percentage was 99.96% for E. coli, 98.23% for E. faecalis and 47.54% for E. faecium. Discussion: Results are presented as pharmacological minimal inhibitory concentration (MIC) values. Ampicillin was applied at the concentration higher than the therapeutic one, which could explain high MIC values for E. coli and E. faecalis. The combination of ampicillin with MKH showed the best improvement of antimicrobial effect on E. faecium (Δ = 29.41%), isolate that was resistant to ampicillin when applied alone. In all the investigated isolates, the combinations with MKH were more effective than ampicillin administered alone. It seems that MKH demonstrates a synergistic antimicrobial activity with ampicillin in vitro, which considerably decreases MIC values for all investigated isolates. These results implicate that MKH could restore the previous activity of ampicillin against some bacteria, which could be a significant benefit for clinical practice.